Development of Economic Activity in Peripheral Regions: Resource and Institutional Potential - Zbigniew NASALSKI (Communications of International Proceedings, 2022)
The aim of the research was to identify the most important conditions for the development of economic activity in peripheral regions, especially in terms of resource and institutional potential. The author's own research was carried out by the method of a diagnostic survey with the use of a questionnaire in enterprises operating in the peripheral regions of north-eastern Poland (in the poviats: Bartoszyce, Braniewo, Ketrzyn and Lidzbark Warminski). In the surveyed enterprises, a significant own (endogenous) potential was found, strengthened by the experience, skills and knowledge of the owners. There is a great determination of entrepreneurs to conduct business in the analyzed poviats, and despite the fact that they operate in peripheral areas. Entrepreneurs in the surveyed counties see the need to strengthen the pro-quality approach in production and services, focus on improving work organization, are aware of the benefits of innovative activities. The respondents preferred investment in machinery to increase production capacity and the creation of own distribution networks, which should result, inter alia, in increasing the value of transactions, increasing the number of customers and increasing market share. The analyzed poviats had a limited labor market, there was a shortage of qualified and adequately motivated employees. Potential employees often showed a lack of interest in taking up a job. The entrepreneurs lacked their own financial resources. A certain disadvantage of the surveyed entities was the low commitment to integration with other economic entities, the lack of strategic partnership and the not very critical approach of entrepreneurs to the "shadow economy". The surveyed entrepreneurs did not take into account the strengthening of cooperation with business environment institutions - in all analyzed poviats little importance was assigned to non-governmental organizations, agricultural advisory centers and economic clusters.
Keywords: business development; peripheral regions; resources; institutions